Lightweight corundum mullite hollow sphere brick and preparation method thereof

By using lightweight corundum mullite hollow ball bricks and combining the premixing and preparation processes of multiple raw materials, the problems of insufficient strength and wear resistance of existing refractory materials are solved, and high-performance refractory products are realized.

CN119330691APending Publication Date: 2025-01-21ZHENGZHOU JINXING REFRACTORY MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411129227.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing lightweight refractory materials have low strength, low thermal stability, and insufficient wear resistance, which cannot meet the needs of dynamic thermal kilns.

Method used

Lightweight corundum-mullite hollow ball bricks are used, including alumina hollow balls, fused mullite, sintered mullite, tabular corundum, Guangxi white mud, aluminum hydroxide, yttrium oxide, silicon carbide and binders. Preparation steps include premixing, billet shaping, baking and sintering.

Benefits of technology

It achieves high strength, low density, low thermal conductivity and good chemical stability, with excellent performance and is suitable for dynamic thermal kilns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004997346740000051
    Figure BDA0004997346740000051
Patent Text Reader

Abstract

The invention relates to a lightweight corundum-mullite hollow sphere brick and a preparation method thereof, and relates to the technical field of refractory materials, the lightweight corundum-mullite hollow sphere brick comprises the following raw materials by weight: 35-40 parts of alumina hollow spheres, 20-30 parts of fused mullite, 5-15 parts of tabular corundum, 9-11 parts of sintered mullite, 3-6 parts of Guangxi white mud, and 5-7 parts of aluminum hydroxide. 0.5-1.5 parts of yttrium oxide, 10-15 parts of silicon carbide and 7-10 parts of a binding agent. The physicochemical index parameters of the light-weight corundum mullite hollow sphere brick provided by the invention are as follows: the volume density is 2.15-2.40, the refractoriness under load is greater than or equal to 1600 DEG C, the thermal shock stability is greater than 20 times, and the normal-temperature compressive strength is gt; the wear resistance is 1t, 70 mpa and 1t; 8-10, the expansion coefficient lt; 0.02, the heat conductivity coefficient at 800 DEG C is 1t; 1W / MK and the heat-resistant strength gt; the performance is excellent, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a lightweight corundum-mullite hollow spherical brick and a preparation method thereof. Background Art

[0002] In the field of materials science, the research on lightweight and high-performance materials has always been one of the hot topics. With the increase in the intensity of green environmental protection governance, the market demand for low-carbon production and energy conservation, emission reduction and consumption reduction has become the main theme of the rapid development of modern industrial technology, especially in the production of cement, lime, zinc oxide, ceramsite sand, alumina, lithium cobalt oxide, bauxite, garbage disposal and other dynamic rotary kilns and high-temperature filtration. The requirements for materials are becoming increasingly stringent. These industries not only require materials to have excellent mechanical properties, such as high strength and wear resistance, but also require materials to have low density, low thermal conductivity and good chemical stability. As an important furnace lining material, lightweight, high-strength and high-wear-resistant refractory products have shown great application potential in the above-mentioned industries and thermal kiln fields due to their unique physical and chemical properties, such as low thermal expansion coefficient, high compressive strength, high creep resistance, excellent wear resistance and strong chemical corrosion resistance.

[0003] Traditional refractory kiln lining brick products often rely on natural resources such as bauxite, kaolin, magnesia, and porcelain stone. The increasing depletion of these resources not only pushes up production costs, but also puts pressure on the natural environment. Therefore, exploring new sources of raw materials and preparation processes to achieve low-cost, high-performance production of refractory materials and extend the service life of furnace lining materials has become an important direction of current research. However, the lightweight refractory materials reported so far cannot meet the use requirements of dynamic thermal kilns (such as various rotary kilns) due to their low strength, low thermal stability, insufficient wear resistance, and short service life. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a lightweight corundum-mullite hollow spherical brick and a preparation method thereof.

[0005] In a first aspect, the present invention provides a lightweight corundum-mullite hollow spherical brick, which comprises the following raw materials in parts by weight:

[0006] 35-40 parts of hollow alumina spheres, 20-30 parts of fused mullite, 9-11 parts of sintered mullite, 10-15 parts of plate-shaped corundum; 3-6 parts of Guangxi white mud, 5-7 parts of aluminum hydroxide, 0.5-1 parts of yttrium oxide, 10-15 parts of silicon carbide, and 7-10 parts of binder.

[0007] Furthermore, the total weight of each raw material in the lightweight corundum-mullite hollow ball brick is 100 parts.

[0008] Furthermore, the particle size of the sintered mullite is 325 meshes, and the particle size of the Guangxi white mud is 180 meshes.

[0009] Furthermore, the particle size of the aluminum hydroxide is 800 mesh, the particle size of the silicon carbide is 325 mesh, and the particle size of the plate-like corundum is 1-3 mm.

[0010] Furthermore, the binder includes at least one of aluminum dihydrogen phosphate and pulp.

[0011] Furthermore, the physical and chemical index parameters of the lightweight corundum mullite hollow ball brick include: bulk density of 2.15-2.40, load softening temperature ≥1600°C, thermal shock stability>20 times, room temperature compressive strength>70MPa, wear resistance<8-10, expansion coefficient<0.02, 800°C thermal conductivity<1W / MK, and compressive strength>20MPA.

[0012] In a second aspect, the present invention provides a method for preparing the lightweight corundum-mullite hollow spherical brick according to any one of the first aspects, the preparation method comprising the following steps:

[0013] Premixing sintered mullite, Guangxi white mud, aluminum hydroxide, yttrium oxide and silicon carbide to obtain a first mixed material;

[0014] Premixing hollow alumina spheres, fused mullite and plate-shaped corundum to obtain a second mixed material;

[0015] Adding a binder to the second mixture and mixing and grinding, and then adding the first mixture and continuing mixing and grinding to obtain a third mixture;

[0016] Forming the third mixed material into a blank to obtain a semi-finished product;

[0017] The semi-finished product is baked and then sintered to obtain the lightweight mullite hollow spherical brick.

[0018] Furthermore, the premixing time is 5-8 minutes; the time for adding the binder to the second mixture and mixing and rolling is 3-5 minutes; and the time for adding the first mixture and continuing mixing and rolling is 10-15 minutes.

[0019] Furthermore, the working condition parameters of the baking include: temperature of 100-200° C., and time of 10-12 hours; the working condition parameters of the sintering include: temperature of 1500-1600° C., and time of 8-10 hours.

[0020] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0021] The embodiment of the present invention provides a lightweight corundum-mullite hollow sphere brick. The physical and chemical index parameters of the lightweight corundum-mullite hollow sphere brick provided by the present invention include: volume density of 2.15-2.4, load softening temperature ≥1600°C, thermal shock stability>20 times, room temperature compressive strength>70mpa, wear resistance<8-10, expansion coefficient<0.02, 800°C thermal conductivity<1W / MK, heat resistance>20MPA, excellent performance, making up for the shortcomings of the prior art. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] In a first aspect, the present invention provides a corundum lightweight mullite hollow spherical brick, wherein the lightweight corundum mullite hollow spherical brick comprises the following raw materials in parts by weight:

[0025] 35-40 parts of hollow alumina balls, 20-30 parts of fused mullite, 5-15 parts of plate-shaped corundum, 9-11 parts of sintered mullite, 3-6 parts of Guangxi white mud, 5-7 parts of aluminum hydroxide, 0.5-1 parts of yttrium oxide, 10-15 parts of silicon carbide, and 7-10 parts of binder.

[0026] The embodiment of the present invention provides a lightweight corundum-mullite hollow sphere brick. The physical and chemical index parameters of the lightweight corundum-mullite hollow sphere brick provided by the present invention include: volume density of 2.15-2.40, load softening temperature ≥1600°C, thermal shock stability>20 times, room temperature compressive strength>70mpa, wear resistance<8-10, expansion coefficient<0.02, 800°C thermal conductivity<1W / MK, heat resistance>20MPA, excellent performance, making up for the shortcomings of the prior art.

[0027] In some specific embodiments, the total weight of each raw material in the lightweight corundum mullite hollow ball brick is 100 parts. When the total weight of each raw material in the lightweight corundum mullite hollow ball brick is 100 parts, if calculated by weight percentage, the lightweight corundum mullite hollow ball brick includes the following raw materials: 35-40% alumina hollow ball, 20-30% fused mullite, 5%-15% plate corundum, 9-11% sintered mullite (powder) (325 mesh), 3-6% Guangxi white mud (powder) (180 mesh), 5-7% aluminum hydroxide powder (800 mesh), 0.5-1% yttrium oxide (rare earth trace element), 10-15% silicon carbide (powder) (180 mesh), 7-10% binder (the binder includes aluminum dihydrogen phosphate and pulp).

[0028] In some specific embodiments, the particle size of the sintered mullite is 325 meshes, and the particle size of the Guangxi white mud is 180 meshes.

[0029] In some specific embodiments, the particle size of the aluminum hydroxide is 800 mesh, the particle size of the silicon carbide is 325 mesh, and the particle size of the plate-like corundum is 1-3 mm.

[0030] In some specific embodiments, the binder includes at least one of aluminum dihydrogen phosphate and pulp.

[0031] In some specific embodiments, the physical and chemical index parameters of the lightweight mullite hollow ball brick include: bulk density of 2.15-2.40, load softening temperature ≥1600°C, thermal shock stability >20 times, room temperature compressive strength >70mpa, wear resistance <8-10, expansion coefficient <0.02, 800°C thermal conductivity <1W / MK, heat resistance >20MPA.

[0032] In a second aspect, the present invention provides a method for preparing the lightweight corundum-mullite hollow spherical brick according to any one of the first aspects, the preparation method comprising the following steps:

[0033] Premixing sintered mullite, Guangxi white mud, aluminum hydroxide, yttrium oxide and silicon carbide to obtain a first mixed material;

[0034] Premixing hollow alumina spheres, fused mullite and plate-shaped corundum to obtain a second mixed material;

[0035] Adding a binder to the second mixture and mixing and grinding, and then adding the first mixture and continuing mixing and grinding to obtain a third mixture;

[0036] Forming the third mixed material into a blank to obtain a semi-finished product;

[0037] The semi-finished product is baked and then sintered to obtain the corundum lightweight mullite hollow spherical brick.

[0038] In some specific embodiments, the premixing time is 5-8 minutes; the time for adding the binder to the second mixture and mixing and grinding is 3-5 minutes; and the time for adding the first mixture and continuing to mix and grind is 10-15 minutes.

[0039] In some specific embodiments, the working condition parameters of the baking include: a temperature of 100-200° C. and a time of 10-12 hours; the working condition parameters of the sintering include: a temperature of 1500-1600° C. and a time of 8-10 hours.

[0040] It should be noted that the raw materials involved in the lightweight corundum-mullite hollow ball bricks and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specifically described, can be directly commercially available products or homemade using existing technologies; the operating steps involved, unless otherwise specified or described, can be performed in a conventional manner in the art or using existing equipment in the art, and will not be described one by one here.

[0041] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0042] Example 1

[0043] This example provides a lightweight corundum mullite hollow ball brick, which is measured by weight. The lightweight corundum mullite hollow ball brick includes the following raw materials: 35 parts of alumina hollow balls, 30 parts of fused mullite, 9 parts of sintered mullite, 3 parts of Guangxi white mud, 5 parts of aluminum hydroxide, 1 part of yttrium oxide, 10 parts of silicon carbide, and 7 parts of binder; the particle size of the sintered mullite is 325 mesh, the particle size of the Guangxi white mud is 180 mesh, the particle size of the aluminum hydroxide is 800 mesh, the particle size of the silicon carbide is 325 mesh, and the binder is aluminum dihydrogen phosphate.

[0044] The preparation method of the light corundum quantized mullite hollow ball brick comprises the following steps:

[0045] Premixing sintered mullite, sintered mullite, Guangxi white mud, aluminum hydroxide, yttrium oxide and silicon carbide for 6 minutes to obtain a first mixed material;

[0046] Premixing the hollow alumina spheres, fused mullite and yttrium oxide for 6 minutes to obtain a second mixture;

[0047] Adding a binder to the second mixture and mixing and grinding for 4 minutes, then adding the first mixture and continuing mixing and grinding for 12 minutes to obtain a third mixture;

[0048] The third mixed material is subjected to blanking and forming, and the parameters of the blanking and forming include: a pressure of 630 MPa to obtain a semi-finished product;

[0049] The semi-finished product is baked at a temperature of 150° C. for 11 hours, and then sintered at a temperature of 1550° C. for 9 hours to obtain the lightweight corundum-mullite hollow spherical brick.

[0050] Example 2

[0051] This example provides a lightweight mullite hollow ball brick, which is measured by weight. The lightweight mullite hollow ball brick includes the following raw materials: 38 parts of alumina hollow balls, 20.5 parts of fused mullite, 15 parts of plate-shaped corundum, 11 parts of sintered mullite, 6 parts of Guangxi white mud, 7 parts of aluminum hydroxide, 0.5 parts of yttrium oxide, 10 parts of silicon carbide, and 7 parts of binder; the particle size of the sintered mullite is 325 mesh, the particle size of the Guangxi white mud is 180 mesh, the particle size of the aluminum hydroxide is 800 mesh, the particle size of the silicon carbide is 325 mesh, and the binder is paper pulp.

[0052] The preparation method of the corundum lightweight mullite hollow spherical brick comprises the following steps:

[0053] Premixing sintered mullite, sintered mullite, Guangxi white mud, aluminum hydroxide, yttrium oxide and silicon carbide for 6 minutes to obtain a first mixed material;

[0054] Premixing the hollow alumina spheres, fused mullite and plate-shaped corundum for 6 minutes to obtain a second mixture;

[0055] Adding a binder to the second mixture and mixing and grinding for 4 minutes, then adding the first mixture and continuing mixing and grinding for 12 minutes to obtain a third mixture;

[0056] The third mixed material is subjected to blanking and forming, and the parameters of the blanking and forming include: a pressure of 630 MPa to obtain a semi-finished product;

[0057] The semi-finished product is baked at a temperature of 150° C. for 11 hours, and then sintered at a temperature of 1550° C. for 9 hours to obtain the lightweight corundum-mullite hollow spherical brick.

[0058] Test Case

[0059] In this example, the lightweight mullite hollow spherical bricks provided in Examples 1 and 2 were subjected to performance testing, and the test results are shown in Table 1.

[0060] Table 1

[0061]

[0062] In summary, the embodiments of the present invention provide a lightweight mullite hollow sphere brick and a preparation method thereof. The physical and chemical index parameters of the lightweight mullite hollow sphere brick provided by the present invention include: bulk density of 2.15-2.40, load softening temperature ≥1600°C, thermal shock stability>20 times, room temperature compressive strength>70mpa, wear resistance<8-10, expansion coefficient<0.02, 800°C thermal conductivity<1W / MK, heat resistance>20MPA, excellent performance, which makes up for the shortcomings of the prior art.

[0063] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0064] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A lightweight corundum mullite hollow ball brick, characterized in that: The lightweight mullite hollow ball brick comprises the following raw materials in parts by weight: 35-40 parts of hollow alumina balls, 20-30 parts of fused mullite, 9-11 parts of sintered mullite, 5-15 parts of plate-shaped corundum, 3-6 parts of Guangxi white mud, 5-7 parts of aluminum hydroxide, 0.5-1 parts of yttrium oxide, 10-15 parts of silicon carbide, and 7-10 parts of binder.

2. The lightweight corundum-mullite hollow ball brick according to claim 1, characterized in that: The total weight of each raw material in the lightweight corundum-mullite hollow ball brick is 100 parts.

3. The lightweight corundum-mullite hollow ball brick according to claim 1, characterized in that: The particle size of the sintered mullite is 325 meshes, and the particle size of the Guangxi white mud is 180 meshes.

4. The lightweight corundum-mullite hollow ball brick according to claim 1, characterized in that: The particle size of the aluminum hydroxide is 800 mesh, the particle size of the silicon carbide is 325 mesh, and the particle size of the plate-like corundum is 1-3 mm.

5. The lightweight corundum-mullite hollow spherical brick according to claim 1, characterized in that: The binder includes at least one of aluminum dihydrogen phosphate and pulp.

6. The lightweight corundum-mullite hollow ball brick according to claim 1, characterized in that: The physical and chemical index parameters of the lightweight corundum mullite hollow ball brick include: bulk density of 2.15-2.40, load softening temperature ≥1600°C, thermal shock stability>20 times, room temperature compressive strength>70mpa, wear resistance<8-10, expansion coefficient<0.02, 800°C thermal conductivity<1W / MK, and heat resistance>20MPA.

7. A method for preparing the lightweight corundum-mullite hollow sphere brick according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Premixing sintered mullite, Guangxi white mud, aluminum hydroxide, yttrium oxide and silicon carbide to obtain a first mixed material; Premixing hollow alumina spheres, fused mullite and plate-shaped corundum to obtain a second mixed material; Adding a binder to the second mixture and mixing and grinding, and then adding the first mixture and continuing mixing and grinding to obtain a third mixture; Forming the third mixed material into a blank to obtain a semi-finished product; The semi-finished product is baked and then sintered to obtain the lightweight corundum-mullite hollow spherical brick.

8. The method for preparing lightweight corundum-mullite hollow sphere bricks according to claim 7, characterized in that: The premixing time is 5-8 minutes; the time for adding the binder to the second mixture and mixing and rolling is 3-5 minutes; the time for adding the first mixture and continuing to mix and roll is 10-15 minutes.

9. The method for preparing lightweight corundum-mullite hollow sphere bricks according to claim 7, characterized in that: The working condition parameters of the baking include: temperature of 100-300° C. and time of 10-12 hours; the working condition parameters of the sintering include: temperature of 1500-1600° C. and time of 8-10 hours.

Citation Information

Patent Citations

  • Ductile mullite brick for pipelines of hot blast stoves and manufacturing method thereof

    CN102249655A

  • High strength and high thermal shock alumina bubble brick and preparation method thereof

    CN103708841A

  • Mullite silicon carbide composite brick with low thermal conductivity and preparation method thereof

    CN105294133A

  • Corundum-mullite brick with high thermal shock stability and preparation method thereof

    CN109574639A

  • Special acid resistant refractory brick and production method thereof

    WO2012119332A1